2022
DOI: 10.3390/su14020628
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and Space Tourism as New Trends in Travelling at the Time of the COVID-19 Pandemic

Abstract: The first European COVID-19 infection was recorded in February 2020, and Poland followed in mid-March. Restrictions were imposed on traveling between states and using public space. These movement restrictions forced a search for new, often innovative, forms of tourism. Google Earth virtual reality (VR), Google Street View, and the Chernobyl VR Project are just some of the selected opportunities to create virtual tours. Different activities using VR mean that people can experience the illusion of travelling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Although virtual tourism has alleviated people's frustration during lockdowns, studies [34][35][36] have shown that it cannot replace inperson tourism in the long run; thus, new tourism provides destinations an opportunity for renewal. Currently, predominant trends include the increasing advancement of extended reality systems, condensed experience-seeking, and interactivity, since new and innovative forms of tourism have emerged as a result of the travel restrictions of 2020 [37]. Extended reality (XR) includes all immersive technologies.…”
Section: Smart Technologiesmentioning
confidence: 99%
“…Although virtual tourism has alleviated people's frustration during lockdowns, studies [34][35][36] have shown that it cannot replace inperson tourism in the long run; thus, new tourism provides destinations an opportunity for renewal. Currently, predominant trends include the increasing advancement of extended reality systems, condensed experience-seeking, and interactivity, since new and innovative forms of tourism have emerged as a result of the travel restrictions of 2020 [37]. Extended reality (XR) includes all immersive technologies.…”
Section: Smart Technologiesmentioning
confidence: 99%
“…COVID-19 pandemic has created and altered different trends in the tourism industry. For example, Polish people use virtual glasses and experience different destinations virtually [14]; real-time on-sight emotional experiences in China [15]. Many people travel in order to get COVID-19 vaccination where they can quickly get it in the early stage of vaccination [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing technical advancement of cyber-physical systems is driving this trend. There have already been a number of initiatives using VR technology to experience and appreciate activities that are either expensive, risky, or geographically unavailable (1).…”
Section: Introductionmentioning
confidence: 99%
“…For the aforementioned reasons and the found vacuum in the existing literature, the current study intends to fill the indicated gap by examining the mediating impact of mental health and performance anxiety on the link between virtual sport experience and endurance performance. Therefore, in line with the gap highlighted and issues broached in the above study, the authors have planned to achieve the following research objectives: (1) To examine the role of Metaverse-based virtual reality sporting experience in determining endurance performance of Chinese athletes; (2) To examine the mediating role of performance anxiety in the relationship between the Metaverse-based virtual reality sporting experience endurance performance of Chinese athletes; and (3) To examine the mediating role of mental health in the relationship between the Metaverse-based virtual reality sporting experience endurance performance of Chinese athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation